Relevance of programming languages in IT - Emirasanov, A. N. (My University, 2021)
All programs that we use every day with our computers are written in one of the programming languages. A programming language is a set of instructions designed to communicate commands to computers. One of the earliest programming languages is Fortran, created in 1954. This language was improved in the following years, and other new languages adopted it as a basis. The main purpose of this language was originally scientific and technical calculations. Almost every language has a compiler, which is responsible for converting the source code into code that a computer can understand. This is because characters are represented on a computer by some numbers called character codes. Each language has its own purpose and capabilities.
Keywords: programming language; computers; character codes; IT industry; IT profession